A Literature Review on the Impact of Socio-Demographic Factors, Differentiated Instruction, and Student Engagement on Mathematics Achievement - Arguillas, Lindy; Arpilleda, Janine Kris; Cabadonga, Vivian (JPAIR Institutional Research, 2026)
This paper presents a comprehensive review of the academic literature concerning the factors that influence student achievement in mathematics. It synthesizes findings on the role of socio-demographic variables, the effectiveness of Differentiated Instruction (DI) as a pedagogical intervention, and the relationship between student engagement and academic outcomes. The review establishes a theoretical basis for the causal links between these factors and student performance, providing a foundation for a quasi-experimental study. It discusses the mixed but often positive effects of socio-demographic factors like parental education, family income, and access to resources, as well as the well-supported positive impact of DI on post-test scores. Furthermore, it highlights the significant positive relationship between behavioral, cognitive, and emotional engagement and mathematics performance. The paper concludes with a detailed methodology section, outlining a quasi-experimental design to empirically test these relationships.
Keywords: Mathematics achievement; Differentiated Instruction; student engagement; socio-demographic factors; quasi-experimental research; academic performance